2008
DOI: 10.5465/amj.2008.31767275
|View full text |Cite
|
Sign up to set email alerts
|

Market Watch: Information and Availability Cascades Among the Media and Investors in the U.S. IPO Market

Abstract: In this study we advance current research on social influence in markets by examining how the recency and availability of information about others' actions within and between different communities influence their allocation of attention and their evaluations. Specifically, we examine how the media and investors allocate attention to and evaluate newly public firms in the days following their initial public offerings (IPOs). Our findings have implications for understanding the fieldwide processes through which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(209 citation statements)
references
References 108 publications
(167 reference statements)
6
201
1
1
Order By: Relevance
“…Although VCFs specialize in making investments in highly promising but highly uncertain growth industries, even for these fi rms the early days of Internet commercialization were extraordinarily novel (Aldrich and Baker, 2001). While all IPOs are uncertain (Pollock and Rindova, 2003;Pollock, Rindova and Maggitti, 2008;Ritter and Welch, 2002), the level of uncertainty surrounding an IPO was magnifi ed for Internet sector fi rms, especially during the mid-to late-1990s when fi rms were going public at an unprecedented rate and at a younger age than had previously been typical. Many fi rms were going public with untried business models and limited revenue streams.…”
Section: Founder-ceo Retention Decisions In a New Industry Contextmentioning
confidence: 99%
“…Although VCFs specialize in making investments in highly promising but highly uncertain growth industries, even for these fi rms the early days of Internet commercialization were extraordinarily novel (Aldrich and Baker, 2001). While all IPOs are uncertain (Pollock and Rindova, 2003;Pollock, Rindova and Maggitti, 2008;Ritter and Welch, 2002), the level of uncertainty surrounding an IPO was magnifi ed for Internet sector fi rms, especially during the mid-to late-1990s when fi rms were going public at an unprecedented rate and at a younger age than had previously been typical. Many fi rms were going public with untried business models and limited revenue streams.…”
Section: Founder-ceo Retention Decisions In a New Industry Contextmentioning
confidence: 99%
“…Prior research has found that media coverage can significantly affect public opinion on firms' actions (Pollock & Rindova, 2003;Pollock, Rindova, & Maggitti, 2008). Hence, we controlled for a firm's public advocacy in favor of GMO approval by counting the number of press releases that biotechnology firms generate about products they submit for USDA approval (firm press releases).…”
Section: Patent Applicants Often List Similar Prior Inventions To Demmentioning
confidence: 99%
“…Accordingly, we propose that the extent to which an actor interacts with other audiences provides a source of information to a focal audience beyond the actor's audiencespecific reputation. Some studies have directly examined the implications of inter-audience information spillover (e.g., Pollock, Rindova, & Maggitti, 2008). For example, actors who are well established with one audience may leverage their intangible assets to obtain advantages with another audience (Jensen, 2003).…”
Section: Hypothesis 2: the (Positive) Contingent Effect Of An Actor'smentioning
confidence: 99%
“…For example, Pollock et al (2008) argue that there is a positive information spillover between different audiences when audiences follow one another to gain information.…”
Section: Theoretical Contributionsmentioning
confidence: 99%